BioSuiteT: A Unified Tool for Biological Sequence Analysis - Victor Terron-Macias; Jezreel Mejia; Mirna Muñoz; Miguel Terron-Hernandez; Miguel Canseco-Perez; Roberto Berrones-Hernández; Yadira Quiñonez (Applied Sciences)
The increasing complexity and fragmentation of bioinformatics tools presents significant challenges for researchers, particularly those without extensive programming expertise. This research presents BioSuiteT v1.0, a unified web-based platform that integrates multiple bioinformatics tools into a single, user-friendly environment. BioSuiteT incorporates twelve core functionalities, including DNA and protein sequence analysis, transcription processes, sequence alignment, BLAST integration, PDB visualization and analysis, phylogenetic tree construction, MOTIFS analysis, and regular expression searching. The platform was developed using the Django framework and MongoDB, following ISO/IEC 29110 standards. Performance testing demonstrated the platform’s capability to handle concurrent users while maintaining stable performance with reduced memory usage. Validation testing involving eight researchers, five bioinformatics experts, and sixty practitioners showed a 95% reduction in technical support requirements compared to traditional installable tools and a 90% reduction in tool switching time. BioSuiteT effectively addresses key challenges identified in bioinformatics software usage, including installation barriers, programming expertise requirements, and tool fragmentation, while maintaining the necessary functionality for biological sequence analysis.